Femtosecond Laser-Fabricated Photonic Chips for Optical Communications: A Review - Chengkun Cai; Jian Wang (Micromachines, 2022)
Integrated optics, having the unique properties of small size, low loss, high integration, and high scalability, is attracting considerable attention and has found many applications in optical communications, fulfilling the requirements for the ever-growing information rate and complexity in modern optical communication systems. Femtosecond laser fabrication is an acknowledged technique for producing integrated photonic devices with unique features, such as three-dimensional fabrication geometry, rapid prototyping, and single-step fabrication. Thus, plenty of femtosecond laser-fabricated on-chip devices have been manufactured to realize various optical communication functions, such as laser generation, laser amplification, laser modulation, frequency conversion, multi-dimensional multiplexing, and photonic wire bonding. In this paper, we review some of the most relevant research progress in femtosecond laser-fabricated photonic chips for optical communications, which may break new ground in this area. First, the basic principle of femtosecond laser fabrication and different types of laser-inscribed waveguides are briefly introduced. The devices are organized into two categories: active devices and passive devices. In the former category, waveguide lasers, amplifiers, electric-optic modulators, and frequency converters are reviewed, while in the latter, polarization multiplexers, mode multiplexers, and fan-in/fan-out devices are discussed. Later, photonic wire bonding is also introduced. Finally, conclusions and prospects in this field are also discussed.